2014
DOI: 10.15740/has/au/9.3/279-287
|View full text |Cite
|
Sign up to set email alerts
|

Constraints and obstacles perceived by extension personnel in application of information and communication technology in agriculture

Abstract: SUMMARY :In India about 760 millions of farmers are engaged in agriculture. According to an estimate more than 60 per cent of the farmers have no access to any source of modern agriculture information. Reaching to these unreached farmers is a great big challenge before the extension system. To achieve growth rate more than four per cent in agriculture, ICT revolution in India must be preceded by the next generation of technology and infrastructure development. Application of ICTs in agriculture should be incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…These findings indicate the efficiency of the private sector in terms of assisting the farming communities and meeting their information needs. These results are in line with a study conducted in India, which also found that farmers prefer to contact private companies and input suppliers because they provide products and inputs in addition to advisory services (Verma et al, 2014).…”
Section: Resultssupporting
confidence: 91%
“…These findings indicate the efficiency of the private sector in terms of assisting the farming communities and meeting their information needs. These results are in line with a study conducted in India, which also found that farmers prefer to contact private companies and input suppliers because they provide products and inputs in addition to advisory services (Verma et al, 2014).…”
Section: Resultssupporting
confidence: 91%
“…Results of our study reported that farmers accessed private agricultural companies and their advisory staff more frequently (87.2%) as compared to public sectors advisory services. These findings are parallel with another similar study reported in India (VERMA et al, 2014) which reported that farmers prefer to consult the private sector's agents as they also provided the required inputs in addition to the advisory services. In this way, the private sector's dealers and suppliers remain connected through the cell phone because of selling their products.…”
Section: Farm Related Use Of Mobile Phonesupporting
confidence: 88%
“…The literature is evident that farmers' characteristics of mobile phone use such as their possession duration and skills and aptitude are closely linked with its adoption and use in agriculture (QIANG et al, 2012). Farmer 's understandings and their basic skills regarding mobile phone use are also considered as mandatory factors for its successful utilizing, as the higher aptitude of mobile phone use increase tendency of accessing agricultural information and hence the farmer's efficiency (VERMA et al, 2014). Our study in this regard has identified the mobile phone usage related characteristics , which included farmers ownership duration and aptitude of the mobile phone.…”
Section: Farmers Attributes Regarding Mobile Phone Usementioning
confidence: 99%
“…Addressing constraints to the use of ICT will encourage more extension officers to use them in their personal and professional duties. Verma et al, (2014) also reported that government and non-government extension officers in India experience some challenges in the use of ICT at different levels. This confirms that constraints to the use of ICT in information dissemination by extension agents is worldwide, though it is more serious in some areas than others.…”
Section: Determinants Of Use Of Ict Tools Among Respondentsmentioning
confidence: 99%
“…The author, thus, concluded that the results have far-reaching implications for designing successful information and extension delivery models by the public, private or by collaborative efforts of the public and the private sector for better delivery of extension services. Verma et al, 2014 concluded that public extension officers were more affected by constraints to ICT use than non-government extension officers.…”
Section: Difference In the Use Of Icts Between Public And Private Extmentioning
confidence: 99%